INSBN alloy and INSB nanowire grown by metal-organic chemical vapor deposition - Jin, Yunjiang (2014)
InSb is a very special binary III-V semiconductor with important applications in infrared detectors, optoelectronics and magnetic field sensors. Attracted by the promising applications for long wavelength infrared range by incorporating a small amount of nitrogen, InSbN alloys were grown by Metal-organic chemical vapor deposition (MOCVD) and characterized with various techniques. The first part of this project deals with growth and characterization of the InSb1-xNx alloys, aiming to reduce the band gap of the alloy. InSb epitaxial layers on InSb substrate were firstly prepared by MOCVD and then the InSbN alloys. Their structural, electrical and optical properties were characterized. It is demonstrated that InSbN alloys can be prepared by MOCVD technique and the concentration of nitrogen in the alloys varies with the growth conditions, including growth temperature and N/(N+Sb) ratio. The effect of GaAs and GaSb substrates on InSbN alloys has also been investigated. The N incorporation, band gap reduction and N distribution of InSbN alloys on the two substrates have been studied carefully. The second part primarily focuses on the growth and characterization of InSb naowires. InSb nanowires were grown on both (100) and (111) InSb substrates under different conditions. Uniform vertical nanowires with high density were obtained on InSb (111) substrate and the growth mechanism was investigated. In addition, despite the large lattice mismatch, InSb nanowires were also successfully realized on GaAs and Si substrates and the growth mechanism was also discussed in detail.